Cybersecurity Strategies for Preventing Ransomware Attacks in Cloud-Based Applications - Ageng Setiani Rafika; Sora Baltasar; Alfri Adiwijaya; Mochamad Heru Riza Chakim; Zhask Stefano Rizky (Pandawan Sejahtera Indonesia, 2025)
Ransomware attacks have become a significant threat to cloud-based applications, posing severe risks to organizations' data integrity, financial stability, and operational continuity. This paper explores the challenges of securing cloud environments against ransomware, focusing on vulnerabilities such as inadequate encryption, weak access controls, and multi-tenancy risks. Through an in-depth analysis, the paper identifies the most common types of ransomware targeting cloud applications, including file encryption and data exfiltration ransomware, and discusses the security weaknesses that facilitate these attacks. The paper further evaluates existing cybersecurity strategies, such as data encryption, multi-factor authentication (MFA), and continuous monitoring, highlighting their effectiveness in preventing ransomware attacks. Based on these findings, a comprehensive framework is proposed, combining technical solutions like strong encryption and AI-based threat detection with organizational practices such as regular employee training and backup solutions. The study also emphasizes the importance of collaboration between cloud service providers and organizations to enhance overall cloud security. By adopting a multi-layered approach and integrating emerging technologies, organizations can significantly improve their resilience against ransomware threats. This research contributes to the ongoing dialogue on cloud security by providing actionable recommendations for preventing ransomware attacks and safeguarding cloud-based applications from evolving cyber threats.